Industry 4.0 readiness and strategic plan failures in SMEs: A comprehensive analysis - Umawathy Techanamurthy; Muhammad Saqib Iqbal; Zulhasni Abdul Rahim (PLoS ONE, 2025)
This study examines the industry 4.0 readiness of 506 Malaysian SMEs, focussing on key factors that contribute to frequent failures in their strategic planning processes. Driven by rapid technological advancements such as IoT, AI, and big data analytics, Industry 4.0 presents opportunities and challenges for SMEs striving to remain competitive in a global digital economy. Despite government efforts such as Malaysia’s Industry4WRD programme, SMEs need help with leadership, digital infrastructure, and workforce competency. This study aims to provide an in-depth analysis of these readiness factors using data from the Industry4WRD assessment framework, evaluating dimensions such as leadership, governance, digital infrastructure, workforce competency, and strategic alignment on a scale of 0–4. The results indicate that leadership and strategic alignment score the highest with a mean of 0.81, while workforce competency scores the lowest at 0.35, highlighting significant competency gaps. Leadership shows a strong positive correlation (0.92) with overall readiness, underscoring its critical role. Sectoral analysis reveals that the chemical sector demonstrates the highest readiness, while Selangor and Johor are the leading regions driven by more robust digital infrastructure. This study emphasises the need for targeted improvements in leadership development, digital infrastructure, and workforce training to bridge readiness gaps, particularly in less developed regions and industries. The findings support the objectives of Malaysia’s New Industrial Master Plan 2030 (NIMP 2030), offering actionable insights for policy makers and leaders of SMEs with the aim of fostering comprehensive digital transformation and strengthening the competitiveness of SMEs in the era of Industry 4.0.